History of Japanese SuperDARN: Initiation of SENSU Syowa radars and progress of Japanese radar project - Sato, Natsuo; Ogawa, Tadahiko; Yamagishi, Hisao; Yukimatu, Akira Sessai; Nishitani, Nozomu; Kikuchi, Takashi; Nozaki, Kenro; Igarashi, Kiyoshi; Nagatsuma, Tsutomu (Polar Science, 2021)
We report the history and progress of the Japanese contribution to the Super Dual Auroral Radar Network (SuperDARN) project; especially focusing on the initial stage of SENSU (Syowa South and East HF Radars of NIPR for SUperDARN) project. The SENSU Syowa South HF radar operated by NIPR was one of the starting members of the initial SuperDARN radar operating at Syowa Station in Antarctica in 1995. It provided bi-directional common-volume observations with the Halley radar. In 1997 the SENSU Syowa East radar was installed. The King Salmon radar organized by NICT was installed in Alaska, USA in 2001. The Hokkaido East radar organized by Nagoya University was installed in Hokkaido, Japan in 2006, and the Hokkaido West radar began operation in 2014. The Japanese group has also contributed to SuperDARN by hosting three SuperDARN workshops in Japan namely: 1) in Tokyo in 1998 hosted by NIPR, 2) in Hokkaido in 2007 hosted by Nagoya University and 3) at Yamanashi in 2019 hosted by NICT. journal article